Strategi Kepala Sekolah dalam persiapan dan pelaksanaan P5 (Proyek Penguatan Profil Pelajar Pancasila) di Sekolah Luar Biasa - Sulistyo, Luluk Bambang; Hidayati, Dian (Academy of Education Journal, 2024)
This research describes several strategies used by school principals to implement the P5 or Strengthening the Profile of Pancasila Students Project, the concepts that students have about Pancasila Students, and the efforts and problems faced during project implementation. In addition, this research explains the preparation plan for starting the P5 project at SLB Muhammadiyah Ponjong. A qualitative descriptive approach was used in this research. Researchers collected data from school principals, teachers and students. The results of this research include first; The principal's strategy to increase the profile of Pancasila students inside and outside the classroom; second; the P5 project is the cultivation of the Pancasila character dimension in learning at school; and third; Some of the obstacles and opportunities in implementing the P5 project include a lack of awareness and understanding of Pancasila values ​​among students. Several obstacles seen from educators include limited time for teaching and learning activities, inappropriate lesson content, and lack of student interest in the subject. The project implementation stages involve socialization, technical training for creating teaching modules and project modules. The project preparation and implementation strategy consists of the first; SWOT analysis, both time allocation and determining profile dimensions. Third, Formation of a project team. Fourth, School Preparation Strategy, Fifth, Determining the project theme according to school readiness. Sixth, Creation of project modules, seventh, evaluation and improvement.